School climate, principal support and collaboration among portuguese teachers - Silva, José Maria Castro (2018)
This article analyses the relationship between school principal support and teacher collaboration among Portuguese teachers. Data were collected from a random sample of 234 teachers in middle and secondary schools. The use of a combined approach using linear and multiple regression tests concluded that the school principal support, through the influence of the variables ‘emotional and informational support’ and ‘support for professional development’, can predict teacher’s involvement in collaboration. This global data is discussed in light of a theoretical framework and compared to data from previous research. The implications of the main findings are discussed and some recommendations are made.